Adoption and practices of occupational health and safety management system in Malaysian construction sites - Chee, Teik Yee (2024)
Construction industry plays a role as an engine of economic growth since it provides job opportunities and generate revenue for both skilled and unskilled citizens. Nevertheless, the rate of occupational accident rate remained high in construction industry. The direct impacts to both the company and workers are discouraged such as loss of productivity and reputation to the company as well as loss of quality of life or premature death. Main cause to poor safety performance may due to the poor safety measure practices, supportive environment, and proper safety management system. The aims of this research are to study on the Occupational Health and Safety Management System (OHSMS) and its relationship with work-related accidents, find out the factors influencing the implementation of OHSMS and work accident at construction industry, also to test the effectiveness and reliability of the safety management system in Malaysia construction site. In this research, a field survey is conducted and 119 number of feedbacks is collected from G7 construction companies in Selangor area. The data is analyzed and evaluated using partial least square structural equation modelling (PLS-SEM) via SmartPLS software. The result revealed that all the variables have positive impact on each other from the result of path coefficient value that nearer to +1 and particularly significant on supportive environment to practices and adoption of OHSMS and importance of the safety measure practices to safety performance from the result of P value which is lower than 0.05.